Influence of animal manure extracts on physico-chemical and nutritional quality of tomatoes grown in soilless cultivation - Luthuli, Ayanda; Magwaza, Lembe Samukelo; Tesfay, Samson Zeray; Magwaza, Shirly; Mditshwa, Asanda (MDPI, 2024)
In response to environmental challenges facing the agricultural sector, growers are moving toward innovative and sustainable cultivation methods such as the hydroponic production system. This study evaluated the effect of different sources of manure on the physico-chemical and nutritional qualities of tomatoes (cv. CLX 532) grown under a hydroponic system. The experiment was set up in a completely randomized design with four treatments, which included three types of animal manure-derived hydroponic nutrient extracts, namely, chicken (CHME), cow (CME) and goat (GME), and a commercial fertilizer as a control. Tomato fruit from each treatment were harvested and analysed for macro- and micronutrients, physicochemical attributes such as total soluble solids (TSS), titratable acidity (TA), total soluble solid to titratable acidity ratio (TSS/TA), BrimA, colour index and firmness. The total phenolics and ascorbic acid content were also assessed. The results showed significant differences in physico-chemical and nutritional quality among different treatments. TSS was higher in CHME (6.47 °Brix) compared to other treatments. The TA was higher in both commercial fertilizer and CHME (0.62% and 0.61%) than in GME and CME (0.44% and 0.39%). Both TSS/TA and BrimA were lower in commercial fertilizer and than in animal manure extracts (AME). CHME had a higher colour index (30.32) while GME had higher firmness (316.9 N) than other treatments. The phenolic content was notably higher in GME compared to the commercial fertilizer and AME. Fruit fertigated with commercial fertilizer had more macronutrient content while fruit fertigated with animal manure-based nutrient solutions had high micronutrients. Based on these findings, animal manure extracts, specifically CHME and GME, can be used as a nutrient source in the production of tomatoes as it produces good fruit quality which is comparable to commercial fertilizers.
Keywords: chicken; cow; goat; fertigation; fertilizer; organic; solution; 30 Agricultural, Veterinary and Food Sciences; 3008 Horticultural Production; 2 Zero Hunger; 30 Agricultural, veterinary and food sciences